P1672IMPACT OF ISLET TRANSPLANTATION VERSUS INSULIN ALONE AFTER KIDNEY TRANSPLANTATION IN TYPE 1 DIABETES PATIENTS. (6th June 2020) - Maanaoui, Mehdi; Chetboun, Mikael; Kerr-Conte, Julie; Gmyr, Valery; Hubert, Thomas; Caiazzo, Robert; Jannin, Arnaud; Le Mapihan, Kristell; Vantyghem, Marie-Christine; Hazzan, Marc; Pattou, François
Abstract: Background and Aims: In patients with type 1 diabetes and end-stage renal disease, kidney transplantation improves both quality of life and survival. When simultaneous kidney-pancreas transplantation appears too invasive, or after failure of the pancreatic graft, an islet after kidney transplantation (IAK) may be considered to restore a stable endocrine function. The aim of our work was to assess the impact of islet transplantation on kidney transplantation outcomes versus insulin alone. Method: In this retrospective parallel-arm cohort study in Lille, we included all type 1 diabetes patients who received a kidney graft from 2000 to 2017, followed by an islet transplantation after kidney (IAK) or not (kidney alone, KA). The primary study endpoint was the change of renal function (estimated glomerular filtration rate, eGFR). Secondary endpoints were glycemic control-related markers, such as HBA1c. Results: During the period of study, 14 patients were included in the KA group versus 15 in the IAK group (including 5 after failure of a simultaneous pancreatic graft) were enrolled. At baseline, kidney donor sex, BMI, cause of death, cold ischemia time and recipient sex, waiting time on dialysis, type of dialysis, and number of previous kidney transplantation, were similar between the two groups. Yet, there were significant differences between KA and IAK, considering donor age (resp. 56.0±15.0 vs 35.2±13.7 years, p<0.001), use of perfusion machine (resp. 7 vs 0, p= 0.002), recipient age (resp. 55.7±5.7 vs 42.1±6.1, p<0.001), and recipient BMI (24.7± 1.8 vs 21.9±2.5 k/m? p=0.004). In IAK, the median (IQR) time between islet and kidney transplantation was 21.8 months (19.0 – 29.4). eGFR was not significantly different at baseline (IAK: 57.8±17.7 vs KA: 48.9±21.4 ml/min, p=0.22) but the decrease was significantly lower up to 5 years in the IAK group (IAK: 0.05±1.99 ml/min/year vs KA: -2.42±3.43 ml/min/year, p=0.03). HBA1c was similar at baseline in both groups (IAK: 7.8±1.6% versus KA: 7.9±1.1%, p=0.31), but significantly lower in the IAK group up to 5 years (IAK: 6.6±0.97% versus KA: 7.8±1.12%, p<0.001). Conclusion: In patients with type 1 diabetes and a functioning kidney graft, IAK was associated with a better glucose control and a slower decrease of eGFR than standard insulin therapy. Our results suggest that IAK should be proposed to type 1 diabetes patients with a functional kidney graft.